Comparison of Simple Additive Weighting and Fuzzy Multi Criteria Decision Making Methods in Determining Scholarship Recipients - Areni Areni; Herlina Latipa Sari; Hari Aspriyono (Jurnal Komputer, Informasi dan Teknologi, 2021)
Madrasah Aliyah Al-Karim is one of the madrasa schools in Central Bengkulu Regency. At the school once a year a scholarship program is held, one of which is a scholarship for the poor. So far, the data management process for prospective scholarship recipients is carried out starting from collecting files for prospective scholarship recipients, then filling in the names of prospective scholarship recipients in Microsoft Word. After that, an assessment of the data of the prospective scholarship recipients is carried out so that the final results can be known who are eligible and who do not deserve the scholarship. Comparison of Simple Additive Weighing and Fuzzy Multi Criteria Decision Making methods in determining scholarship recipients at Madrasah Aliyah Al-Karim is done by comparing the final results and processing time obtained from the results of applying the two methods based on the assessment data of each prospective scholarship recipient. In helping the comparison process of the two methods, an application was built using the Visual Basic .Net programming language and SQL Server database, where with the application you will see the comparison results of the Simple Additive Weigthing and Fuzzy Multi Criteria Decision Making methods. Based on the black box testing that has been carried out, the results obtained are that the functionality of the application runs as expected